Los Zetas Inc.: criminal cooperations, energy and civil war in Mexico - Correa-Cabrera, Guadalupe (University of Texas Press, 2017)
The Zetas' origins -- The Zetas' war -- A transnational criminal corporation -- Paramilitarization of organized crime and a "war on drugs" -- The new paramilitarism in Mexico -- Mexico's modern civil war -- The Zetas' war and Mexico's energy sector -- Energy and security in Tamaulipas, ground zero for the Zetas -- Who benefits from the Zetas' war? -- Conclusion. Four successful business models in an era of modern civil wars -- Appendix I. Energy reform and the Zetas' expansion (timeline) -- Appendix II. History of organized crime in Tamaulipas : timeline of key events -- Appendix III. Criminal paramilitaries and natural resources in Mexico (map) -- Appendix IV. El Disfraz de la Guerra (the war's disguise) : communiqué by residents of La Riberen̋a -- Appendix V. Organizational charts : constellis holdings, LLC and Los Zetas Inc -- Appendix VI. Areas of dominant influence of major TCOs in Mexico, 2015